2000
DOI: 10.1677/joe.0.1650617
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor in response to high glucose in rat mesangial cells

Abstract: Diabetic nephropathy associated with hyperglycemia is characterized by glomerular hyperfiltration and endothelial dysfunction. Vascular endothelial growth factor (VEGF) is known to be primarily involved in neoangiogenesis and increased endothelial permeability. The purpose of this study was to investigate VEGF expression in response to high glucose in rat cultured mesangial cells and to identify its signal pathway via protein kinase C (PKC). Rat mesangial cells were cultured with different concentrations of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
3
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 19 publications
(16 reference statements)
3
47
3
1
Order By: Relevance
“…In combination, however, our two studies' data suggest that modulation of glomerular angiogenesis by iNOS-derived NO may be more central in explaining the increased glomerular damage than altered intraglomerular coagulation or even be a causative factor for enhancing local coagulation, respectively. Consistent with this interpretation is the fourth major finding, namely that L-NIL treatment specif-ically reduced glomerular VEGF receptor mRNA expression and VEGF binding sites in early anti-Thy 1.1 GN, whereas it did not affect the glomerular overproduction of VEGF, which is confined to mesangial cells and/or podocytes (10,(33)(34)(35)(36)(37)(38). Our data do not allow us to dissect the question of whether reduced endothelial proliferation led to reduced VEGF receptor expression or vice versa.…”
Section: Discussionmentioning
confidence: 57%
“…In combination, however, our two studies' data suggest that modulation of glomerular angiogenesis by iNOS-derived NO may be more central in explaining the increased glomerular damage than altered intraglomerular coagulation or even be a causative factor for enhancing local coagulation, respectively. Consistent with this interpretation is the fourth major finding, namely that L-NIL treatment specif-ically reduced glomerular VEGF receptor mRNA expression and VEGF binding sites in early anti-Thy 1.1 GN, whereas it did not affect the glomerular overproduction of VEGF, which is confined to mesangial cells and/or podocytes (10,(33)(34)(35)(36)(37)(38). Our data do not allow us to dissect the question of whether reduced endothelial proliferation led to reduced VEGF receptor expression or vice versa.…”
Section: Discussionmentioning
confidence: 57%
“…Counting of cell number. An index of cell proliferation was determined using a WST-1 (4-[3-(4-iodophenyl)-2-(4-nitrophenyl)-2H-5-tetrazolio]-1,3-benzene disulfonate) cell-counting kit, which is similar to the MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay (Wako, Osaka, Japan) (5,6,28). Endothelial cells were seeded onto uncoated 96-well tissue culture plates (Corning, NY).…”
Section: Methodsmentioning
confidence: 99%
“…On the other side, vascular endothelial growth factor (VEGF), one of the strongest hyperpermeability inducers (Senger et al 1990), plays a critical role in both physiological and pathological hyperpermeability (Bates and Harper 2002). Overexpression of VEGF was found in the progression of nephritic and ophthalmic complications in diabetes (Kim et al 2000;Cukiernik et al 2004). The molecular mechanism involved in the permeability alteration induced by VEGF in diabetic condition is not clear; however, there are evidences indicating that caveolae was indispensable to the process, and it was suggested that VEGF-induced permeability was mediated by caveolae (Feng et al 1999).…”
Section: Introductionmentioning
confidence: 99%